A self-sustainable solar desalination system using direct spray technology. (15th August 2020) - Chen, Qian; Alrowais, Raid; Burhan, Muhammad; Ybyraiymkul, Doskhan; Shahzad, Muhammad Wakil; Li, Yong; Ng, Kim Choon
Abstract: Solar desalination offers a sustainable solution to growing global water demand due to the geographical coincidence between high solar availability and severe water scarcity. This paper presents a self-sustainable solar desalination system combining a spray-assisted low-temperature desalination system, solar thermal collectors, and heat storage tanks. A mathematical model is firstly developed and validated with laboratory pilot for the proposed large-scale solar-powered desalination system. Afterward, the long-term productivity and energy efficiency of the system is evaluated under the climatic conditions of Makkah, Saudi Arabia. The proposed solar desalination system is able to provide an uninterrupted water supply of 20 kg/day for per square meter solar collector area, and the value can be further increased by optimizing the interactions of the three subsystems, i.e. efficiency of the solar collectors, temperature and heat losses in the storage tank, and energy efficiency of the desalination system. With a collector area of 360 m 2, the annual productivity is maximized when the feed flowrate is 1.7 kg/s and the diameter of the heat storage tank is 1.9 m. The desalination cost is estimated to be $1.29/m 3, which is much lower than other solar thermal desalination systems. Highlights: A solar-driven low-temperature desalination system has been evaluated. Long-term desalination performance has been predicted using dynamic meteorological data. The optimal design and operational parameters have been obtained. The proposed solar desalination is cost-effective compared with other solar desalination processes.